Combating Ukraine’s Health Crisis : Lessons from Europe - Menon, Rekha (World Bank, Washington, DC, 2012)
This knowledge brief synthesizes the important findings of a recent study. It spotlights key issues and challenges facing Ukraine's health sector and suggests strategies for improvement. To combat the current health crisis, Ukraine could look at the lessons learned by other European countries that have faced similar health crises.